Flow topology and thermal mechanism in turbulent channel flow with tapered V-shaped baffles - Somchai Sripattanapipat; Naman Jain; Suvanjan Bhattacharyya; Varesa Chuwattanakul; Paisarn Naphon; Smith Eiamsa-ard (Case Studies in Thermal Engineering, 2025)
Solar air heaters (SAHs) are widely employed in applications that demand low to moderate temperature thermal energy, such as space heating in residential and commercial buildings, agricultural crop drying, and various industrial processes. A key consideration in the advancement of SAH technology is the enhancement of heat transfer between the absorber surface and the airflow, which directly influences thermal efficiency and overall system performance. In this study, a numerical investigation is conducted to analyze turbulent periodic flow and heat transfer enhancement in a three-dimensional channel fitted with regularly spaced tapered V-shaped baffles (T-VBs). The simulations are performed using the finite volume method in conjunction with the SIMPLE algorithm, and the Generalized k-ω (GEKO) turbulence model is employed to capture the flow dynamics. The analysis examines the effects of varying blockage ratios at their V-back end (BRb = 0.2 to 0.3) and V-apex front (BRf = 0.0 to 0.3) across a range of Reynolds numbers (3,000–20,000). Key dimensionless parameters, including the Nusselt number (Nu), friction factor (f), and thermal performance factor (η), are evaluated. The findings indicate that T-VBs achieve comparable Nusselt numbers to conventional V-shaped baffles (VBs) for Reynolds numbers above 8,000, while consistently demonstrating lower frictional losses. An increased BRb enhances heat transfer, but the impact of BRf varies depending on the Reynolds number and BRf values. Friction losses rise with increasing BRb and BRf, yet remain lower for T-VBs than VBs. A maximal η, 2.49, is achieved at BRf = 0.01 and BRb = 0.2 for Re = 3,000, emphasizing the potential of T-VBs in optimizing thermal performance. The results suggest that T-VBs, with optimized geometries, offer a promising alternative to VBs for enhancing heat transfer and reducing energy consumption.